The Methods of Moral Education in Lithuanian Folk Pedagogy - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2007)
In the article there are discussed the methods of moral education applied in Lithuanian folk pedagogy. The methods of a child education mostly depended on the dominating concept of childhood and the nature of the child in the culture. In the article is discussed the application of narrative methods in traditional practice. Folk pedagogy widely uses narrative (verbal) methods whose essence is revealed in the statement "A parents’ word (also other adults’) is sacred". Two groups of verbal methods are determined: suasion encompassing explanations, advice, convincing, moralising, and prohibitions often supported by beliefs, warnings and intimidations. The importance of folk art as a universal means educating both through the content and through the methods of application is stressed. Besides traditional methods used for educating children, stimulation methods, punishment and rewards, are analysed. A child in a traditional culture often is considered morally inferior, given to sin or else sinful by birth therefore methods of education were focused on elimination and suppression of inappropriate inclinations and instances of behaviour. Punishments consisting of scolding, cursing, mocking, intimidating, physical punishments made up a big part of educational methods. In the article emphasizes the damage produced by intimidation which affected not only the emotional sphere but also the formation of the negative attitude towards religion, environment and other people. Physical punishment in the practice of traditional moral education were interpreted as an inseparable part and even necessity. The attitude to the punishment as to the necessity is expressed in the saying that "one punished is worth 10 unpunished". However, folk pedagogy cannot be reduced to the pedagogy of stick and carrot. Stick was resorted to as the last instance, when the other measures of education gave no effect. A much greater effect than a punishing stick produced the conviction that no breech of moral norms or standards of moral behaviour will remain unnoticed. Good behaviour in traditional culture was taken for granted, which does not have to be specifically brought to notice, therefore gifts and rewards for good behaviour often were seen as spoiling measures in child education and as methods of encouragement were applied only in exceptional cases. The application of the methods was determined by many factors: one or other interpretation of a child’s nature, a child’s age, concrete situation etc. Very important is the context of application of the methods. The effectiveness of the methods was determined by how timely and appropriate were methods, e.g.: in some cases a fairy tale was meant only for listening, in other instances the very same fairy tale turned into an important moral, when a deserved punishment fostered the need not to break the rules while unnecessary physical punishment taught how best to hide misdemeanours.